Yes, not now, or never: an analysis of reasons for refusing or accepting emergency department-based take-home naloxone. Issue 2 (23rd May 2018) - Kestler, Andrew; Giesler, Amanda; Buxton, Jane; Meckling, Gray; Lee, Michelle; Hunte, Garth; Wilkins, Jacob; Marks, Dalya; Scheuermeyer, Frank
Abstract: Objective: Take-home naloxone (THN) reduces deaths from opioid overdose. To increase THN distribution to at-risk emergency department (ED) patients, we explored reasons for patients' refusing or accepting THN. Methods: In an urban teaching hospital ED, we identified high opioid overdose risk patients according to pre-specified criteria. We offered eligible patients THN and participation in researcher-administered surveys, which inquired about reasons to refuse or accept THN and about THN dispensing location preferences. We analyzed refusal and acceptance reasons in open-ended responses, grouped reasons into categories (absolute versus conditional refusals, ) then searched for associations between patient characteristics and reasons. Results: Of 247 patients offered THN, 193 (78.1%) provided reasons for their decision. Of those included, 69 (35.2%) were female, 91 (47.2%) were under age 40, 61 (31.6%) were homeless, 144 (74.6%) reported injection drug use (IDU), and 131 (67.9%) accepted THN. Of 62 patients refusing THN, 19 (30.7%) felt "not at risk" for overdose, while 28 (45.2%) gave conditional refusal reasons: "too sick, " "in a rush, " or preference to get THN elsewhere. Non-IDU was associated with stating "not at risk, " while IDU, homelessness, and age under 40 were associated with conditional refusals. Among acceptances, 86 (65.7%) mentioned saving others as a reason. Most respondents preferred other dispensing locations beside the ED, whether or not they accepted ED THN. Conclusion: ED patients refusing THN felt "not at risk" for overdose or felt their ED visit was not the right time or place for THN. Most accepting THN wanted to save others. RÉSUMÉ: Objectif: L'utilisation de la naloxone à domicile (ND) permet de diminuer la mortalité liée aux surdoses d'opioïdes. L'étude visait donc, dans le contexte d'une distribution accrue de ND parmi les patients à risque traités au service des urgences (SU), à examiner les motifs de refus ou d'acceptation de l'offre d'utilisation extrahospitalière de l'antidote. Méthode: Les patients traités dans un SU d'un hôpital d'enseignement situé en milieu urbain et connaissant un risque élevé de surdoses d'opioïdes ont fait l'objet d'une sélection selon des critères prédéterminés. Les patients admissibles se sont vu offrir de la ND et la possibilité de participer à une enquête menée par des chercheurs, sur les motifs de refus ou d'acceptation de la ND et sur les préférences quant aux lieux de distribution de la ND. Après la collecte des réponses aux questions ouvertes, il y a eu analyse des motifs de refus ou d'acceptation, catégorisation des motifs (refus absolus ou conditionnels) et recherche d'associations entre les motifs et les caractéristiques des patients. Résultats: Sur 247 patients qui se sont vu offrir de la ND, 193 (78, 1 %) ont fourni leurs motifs de décision. Parmi les sujets retenus, il y en avait 69 (35, 2 %) qui étaient des femmes, 91 (47, 2 %) qui étaient âgés de moins de 40 ans, 61 (31, 6 %) qui étaient des sans-abris, 144 (74, 6 %) qui faisaient usage de drogues injectables (UDI) et 131 (67, 9 %) qui ont accepté l'offre de ND. Sur les 62 patients qui ont refusé l'offre de ND en cas de surdose, 19 (30, 7 %) se considéraient comme « non à risque » et 28 (45, 2 %) autres ont invoqué des motifs conditionnels de refus : « trop malades », « trop pressés » ou autre lieu de distribution de la ND. Le non-UDI était associé à l'énoncé « non à risque », tandis que l'UDI, le sans-abrisme et un âge inférieur à 40 ans étaient associés à des refus conditionnels. Parmi les patients qui ont accepté l'offre, 86 (65, 7 %) ont indiqué, comme motif, le fait de sauver la vie d'autres personnes. La plupart des répondants préféraient d'autres lieux de distribution au SU, quelle que soit leur réponse à l'offre de ND. Conclusions: Les patients au SU qui ont refusé l'offre de ND en cas de surdose se considéraient comme « non à risque » ou estimaient que ce n'était pas le bon moment ou la bonne place pour discuter de la ND. La plupart de ceux qui ont accepté l'offre de ND voulaient sauver la vie d'autres personnes.